A Descriptive Study of Fertility-Related Quality of Life in Women Receiving Infertility Treatment - Siti Jihan Afifah; Hilma Putri Lubis; Irma Sepala Sari Siregar; Mutiara Indah Sari (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Objective: This study aimed to describe fertility-related quality of life among women with infertility who are undergoing fertility treatment at a single tertiary fertility center, based on sociodemographic, clinical, and treatment characteristics.Methods: The study design was descriptive with a cross-sectional approach, using a consecutive sampling technique. The study sample consisted of infertile women undergoing pregnancy programs at Halim Fertility Center (HFC) RSIA Stella Maris Medan and met the inclusion and exclusion criteria. Data were collected using the FertiQoL (Fertility Quality of Life Tool) questionnaire and were presented as a frequency distribution. Results: Of the 60 respondents, most were in the 31–35 age group (38.3%) and were overweight (55%), followed by normal weight (41.7%). Most of them experienced primary infertility (83.3%), with infertility lasting 2–5 years (41.7%), and the most common cause was ovulation disorders (31.7%). Based on the type of pregnancy program, In Vitro Fertilization (76.7%) was the most common procedure. FertiQoL assessment revealed a wide range of fertility-related quality-of-life scores across treatment options.Conclusion: Most women undergoing infertility treatment reported a high fertility-related quality of life (60%), with higher average scores seen in those undergoing in vitro fertilization (58.7%). AbstrakTujuan: Penelitian ini bertujuan untuk menggambarkan tingkat kualitas hidup terkait fertilitas pada wanita infertil yang menjalani program kehamilan berdasarkan karakteristik sosiodemografi, klinis, dan jenis terapi. Metode: Desain penelitian adalah deskriptif dengan pendekatan cross-sectional menggunakan teknik consecutive sampling. Sampel penelitian adalah wanita infertil yang menjalani program kehamilan di Halim Fertility Center (HFC) RSIA Stella Maris Medan serta memenuhi kriteria inklusi dan eksklusi. Data dikumpulkan menggunakan kuesioner FertiQoL (Fertility Quality of Life Tool) dan disajikan dalam bentuk distribusi frekuensi.Hasil: Dari 60 responden, mayoritas berada pada kelompok usia 31 – 35 tahun (38,3%) dan memiliki status berat badan berlebih (55%) dan diikuti normoweight (41,7%). Sebagian besar responden mengalami infertilitas primer (83,3%) dengan durasi infertilitas 2 – 5 tahun (41,7%), dan penyebab tersering adalah gangguan ovulasi (31,7%). Berdasarkan jenis program kehamilan, Fertilisasi In Vitro (76,7%) merupakan prosedur yang paling banyak dilakukan. Pengukuran menggunakan FertiQoL menunjukkan bahwa responden memiliki kualitas hidup yang bervariasi. Kesimpulan: Hasil penelitian menunjukkan bahwa sebagian besar wanita infertil yang sedang menjalani program kehamilan memiliki kualitas hidup tinggi (60%), dengan proporsi tertinggi pada kelompok Fertilisasi In Vitro (58,7%).